2012
DOI: 10.1007/s00706-012-0760-2
|View full text |Cite
|
Sign up to set email alerts
|

Different coordination modes and supramolecular aggregations in copper(II) pentane-2,4-dionato compounds with 2-pyridone and 3-hydroxypyridine

Abstract: Copper(II) bis(pentane-2,4-dionato-j 2 O,O 0 ) compounds with 2-pyridone (1) and 3-hydroxypyridine (2) were prepared by the reaction of bis(pentane-2,4-dionato-j 2 O,O 0 ) copper(II) with selected ligands. The coordination of Cu(II) in both compounds is square pyramidal with the fifth coordination site occupied by the carbonyl oxygen atom of the 2-pyridone ligand in 1 and by the nitrogen atom of 3-hydroxypyridine in 2. The X-ray crystallographic studies revealed different crystal aggregation influenced by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…This was further confirmed by the blueshift of the C−O stretching vibration from 1015 to 1021 cm −1 after HMF interacted with the catalyst [36] . At the same time, the C=O stretching vibration in HMF was observed to blueshift from 1658 to 1670 cm −1 (Δ ν 12 cm −1 ) due to the HMF‐catalyst interaction, which indicated that the oxygen of aldehyde was strongly adsorbed on the metal surface and the C=O bond was strengthened accordingly [37] . Apart from that, the vibrations attributed to the C=C (1520 cm −1 ) and C−C=C (1187 cm −1 ) bonds of furan ring remained unchanged during the HMF‐catalyst interaction, which suggested no obvious interaction between furan ring and the catalyst surface.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…This was further confirmed by the blueshift of the C−O stretching vibration from 1015 to 1021 cm −1 after HMF interacted with the catalyst [36] . At the same time, the C=O stretching vibration in HMF was observed to blueshift from 1658 to 1670 cm −1 (Δ ν 12 cm −1 ) due to the HMF‐catalyst interaction, which indicated that the oxygen of aldehyde was strongly adsorbed on the metal surface and the C=O bond was strengthened accordingly [37] . Apart from that, the vibrations attributed to the C=C (1520 cm −1 ) and C−C=C (1187 cm −1 ) bonds of furan ring remained unchanged during the HMF‐catalyst interaction, which suggested no obvious interaction between furan ring and the catalyst surface.…”
Section: Resultsmentioning
confidence: 65%
“…[36] At the same time, the C=O stretching vibration in HMF was observed to blueshift from 1658 to 1670 cm À 1 (Δν 12 cm À 1 ) due to the HMF-catalyst interaction, which indicated that the oxygen of aldehyde was strongly adsorbed on the metal surface and the C=O bond was strengthened accordingly. [37] Apart from that, the vibrations attributed to the C=C (1520 cm À 1 ) and CÀ C=C (1187 cm À 1 ) bonds of furan ring remained unchanged during the HMFcatalyst interaction, which suggested no obvious interaction between furan ring and the catalyst surface. The CÀ OÀ C vibration located at 1070 cm À 1 was overlapped by those of CÀ O stretching vibration from EtOH, [36] which cannot be recognized.…”
Section: Chemsuschemmentioning
confidence: 89%
“…In the case of an N-bound hpy ligand, the N atom cannot act as a hydrogen-bond acceptor and the dimensionality can thus be rather limited even though the -OH group can be freely involved in the formation of the hydrogenbonded network. In the case of -diketonates, this can be seen, for example, in the trigonal bipyramidal [Zn(tfpb) 2 (hpy-N)] (Ma et al, 2007) and square-pyramidal [M(acac) 2 (hpy-N)] (M = Cu, Zn) (Ma et al, 2006;Perdih, 2012) complexes, where only hydrogen-bonded dimers and chains are formed, respectively, and where only the O atoms of the -diketonates act as hydrogen-bond acceptors since the bonded N atom cannot participate. On the other hand, in the case of an Obound hpy ligand, the -OH group and the N atom can both participate in hydrogen bonding, as was observed in (II), where a layered network is formed.…”
Section: Figurementioning
confidence: 99%
“…In our previous research we have been interested in the formation of non-covalent forces such as classical hydrogen bonds as well as C-HÁ Á ÁO/ and Á Á Á interactions (Perdih, 2012a,b,c; Koleša-Dobravc et al, 2014, 2015a,b) since they have been demonstrated as important tools for assembling molecules in crystal lattices. We have to be aware that prediction of crystal arrangement remains difficult since intermolecular forces which influence the supramolecular selfassembly in the solid state are very often comparatively weak.…”
Section: Introductionmentioning
confidence: 99%